Finding needles in a haystack: identification of inter-specific introgressions in wheat genebank collections using low-coverage sequencing data - Keilwagen, Jens; Lehnert, Heike; Badaeva, Ekaterina D.; Özkan, Hakan; Sharma, Shivali; Civáň, Peter; Kilian, Benjamin (Frontiers in Plant Science, 2023)
Recently, entire genebank collections of wheat have been extensively characterized with sequencing data. We have identified introgressions using these genotyping-by-sequencing and whole-genome sequencing data. On the basis of our results, we provide information about predicted introgressions at 1-Mb resolution for 9,172 wheat samples as a resource for breeders and scientists. We recommend that all plant genetic resources, including genebank collections, be characterized using a combination of variant calling and introgression prediction. This is necessary to identify potential duplicates in collections efficiently and reliably, and to select promising germplasms with potentially beneficial introgressions for further characterization and prospective breeding application.